2013
DOI: 10.1186/1471-2458-13-578
|View full text |Cite
|
Sign up to set email alerts
|

Are environmental characteristics in the municipal eldercare, more closely associated with frequent short sick leave spells among employees than with total sick leave: a cross-sectional study

Abstract: BackgroundIt has been suggested that frequent-, short-term sick leave is associated with work environment factors, whereas long-term sick leave is associated mainly with health factors. However, studies of the hypothesis of an association between a poor working environment and frequent short spells of sick leave are few and results are inconsistent. Therefore, we aimed to explore associations between self-reported psychosocial work factors and workplace-registered frequency and length of sick leave in the elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…We included only sickness absence of >3 weeks duration and had no information regarding the cause of the absence. Thus our results may not generalize to sickness absence of shorter duration, which may have other mechanisms (62,63). We also do not know if the examined associations vary in relation to the cause of absence.…”
Section: Discussionmentioning
confidence: 54%
“…We included only sickness absence of >3 weeks duration and had no information regarding the cause of the absence. Thus our results may not generalize to sickness absence of shorter duration, which may have other mechanisms (62,63). We also do not know if the examined associations vary in relation to the cause of absence.…”
Section: Discussionmentioning
confidence: 54%
“…Unfortunately, Munir and colleagues did not investigate the frequency of SA episodes. Stapelfeldt et al [29] found that the COPSOQ leadership quality scale was cross-sectionally associated with the frequency of long (C15 days) SA episodes. This corroborates our finding that leadership quality improved discrimination by both the SA days and SA episodes model.…”
Section: Cross-national Validation and Updating Of The Sa Episodes Modelmentioning
confidence: 98%
“…We assume that an intervention focusing on the core task at work will reduce unreasonable and unnecessary tasks, which subsequently will reduce employees' stress level leading to a lower incidence of short-term sickness absence. It has been suggested that short-term sickness absence may partly be a reaction, either health-or coping-based or both, to a problematic psychosocial work environment (17)(18)(19). Long-term sickness absence, on the other hand, may more often be related to severe diseases (20).…”
mentioning
confidence: 99%